Cephalosporin prescriptions for outpatients in 12 primary medical institutions in a county of Zhejiang province, 2016 - 2020: an analysis on outpatient prescription records - Shiyu HAN; Xiaolian DONG; Yingying WANG; Yingfeng CHEN; Na WANG; Fei YAN; Chaowei FU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo investigate cephalosporin prescriptions in outpatient settings within primary medical institutions in a county of Zhejiang province from 2016 to 2020 for standardizing the clinical application of cephalosporins. MethodsThe outpatient prescription records of 4 community health service centers and 8 township health centers in the county from 2016 to 2020 were obtained through the data sharing platform of medical institutions. The cephalosporin prescriptions for each year were documented, and the trends in cephalosporin prescription patterns were analyzed using linear regression analysis. Changes in the age, gender, reasons for medication, and route of administration associated with cephalosporin prescriptions during the 5-year period were examined using a chi-square test. ResultsDuring the period, a total of 163 527 outpatient prescriptions were issued by the 12 medical institutions, with 30 459 of them being for antibiotics. The mean annual proportion of antibiotic prescriptions was 19.03%. The annual proportion of antibiotic prescriptions showed a significant downward trend (β = - 1.09, P < 0.001), as well as the cephalosporin prescriptions (β = - 4.81, P = 0.012) during the period. The proportion of cephalosporin prescriptions for outpatients exhibited a seasonal variation, with a higher proportion observed during the winter season and a lower one during the summer season. In terms of the Anatomical Therapeutic Chemical classification, there was a significant decline in the prescription rates of first-generation cephalosporins (β = - 11,965.35, P = 0.047), while second-generation cephalosporins exhibited an upward trend (β = 4,041.92, P = 0.003) and emerged as the dominant choice for prescribing, with cefuroxime and cefaclor being among the most frequently prescribed second-generation cephalosporins. The majority of cephalosporin prescriptions were allocated for the treatment of respiratory infections, while there was a gradual increase in outpatient prescriptions for oral administration of cephalosporins and individuals aged 60 years and above during the period. ConclusionThe prescriptions of cephalosporins for outpatients in the primary hospitals of the county were generally rational.